1991
DOI: 10.1111/j.1432-1033.1991.tb16261.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of early‐response genes by hydrogen peroxide in a mouse osteoblastic cell line

Abstract: HzOZ, like other oxidants, is known to act as a mitogen at low concentrations in resting Balb/3T3 or mouse epidermal JB6 cells. We described previously that H 2 0 2 induces some early response genes in Balb/3T3 cells. We extended these observations using another cell line, MC3T3 (mouse osteoblastic) cells by examination of transcriptional activity of these genes and by using inhibitors of protein kinases. H2O2 increased the expressions of c-fos, c-jun, egr-1 and JE genes which are known to be early response ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(105 citation statements)
references
References 67 publications
4
101
0
Order By: Relevance
“…Recent reports showed that c-Jun mRNA is induced by low H202 concentrations in HeLa cells (72) and in an osteoblastic cell line (73). In HeLa cells, treatment with 250 /zM H202 for several hours could also elicit AP-1 binding activity.…”
Section: How Specific Is Pdtc?mentioning
confidence: 99%
“…Recent reports showed that c-Jun mRNA is induced by low H202 concentrations in HeLa cells (72) and in an osteoblastic cell line (73). In HeLa cells, treatment with 250 /zM H202 for several hours could also elicit AP-1 binding activity.…”
Section: How Specific Is Pdtc?mentioning
confidence: 99%
“…Indeed, many normal cells exposed to H 2 O 2 exhibit increased proliferation and express growth-related genes (42)(43)(44). Furthermore, given that tumor cells produce large amounts of H 2 O 2 (45,46), this metabolite might also promote tumor cell proliferation.…”
Section: In Vitro Inactivation Of Pten By H 2 O 2 Is Accompanied By Tmentioning
confidence: 99%
“…From the sequence analysis of transcription factor binding sites in the PRE, the sequence of Elk1, which is the serum response factor accessory protein (25), was located between Ϫ533 and Ϫ520 of the SOD1 gene (24). Induction by H 2 O 2 of c-fos and possibly other early response genes was mediated through the activation of the serum response element for the binding site of serum response factor (26). The Ϫ533 to Ϫ520 sequence named as the HRE was tested for induction ability by H 2 O 2 .…”
Section: Activation Of the Sod1 Promoter By Hydrogen Peroxide Pqmentioning
confidence: 99%